Nivolumab‐related tracheobronchial chondritis: Extremely rare manifestation of an immune‐related adverse effect. Issue 11 (5th September 2020) - Kuba, Kiyomi; Nakahira, Mitsuhiko; Inoue, Hitoshi; Kogashiwa, Yasunao; Ebihara, Yasuhiro; Sugasawa, Masashi
Abstract: Background: Programmed death‐1 checkpoint inhibitors, such as nivolumab, have successfully been utilized for recurrent or metastatic squamous cell carcinoma of the head and neck; however, their use may be associated with immune‐related adverse effects (irAEs). Methods: We describe a case of tracheobronchial chondritis as a rare irAE in a 72‐year‐old man with multiple pulmonary metastases of hypopharyngeal squamous cell carcinoma treated with nivolumab, who was seen with a 2‐week history of fever, nonproductive cough, and dyspnea. Results: CT revealed a thickened tracheobronchial wall and narrowed intraluminal space resulting in respiratory symptoms, despite significant clinical response of the metastases. He was clinically diagnosed with tracheobronchial chondritis and treated successfully by steroid therapy. His diagnosis was confirmed by a positive serum anti‐collagen type 2 antibody test. Conclusions: In addition to interstitial lung disease, tracheobronchial chondritis should be considered as a possible irAE in patients with acute respiratory symptoms after nivolumab administration.